Adjustable suture as a method of guarded filtration in trabeculectomy – review of current techniques - Jurowski, Piotr; Gajdowska, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Filtration surgery has evolved during the last decades. Guarded filtration surgery especially adjustable and releasable suture techniques are significant advancement in conventional trabeculectomy. The aim of this article is to provide a survey of currently used methods of adjustable suture with respect to main trabeculectomy techniques.